Alleviating Interference through Cognitive Radio for LTE-Advanced Network - Tsung-Hui Chuang; Guan-Hong Chen; Meng-Hsun Tsai; Chun-Lung Lin (International Journal of Electrical and Computer Engineering (IJECE), 2015)
In the LTE-Advanced network, some femtocells are deployed within a macroecell for improving throughput of indoor user equipments (UEs), which are referred to as femtocell UEs (FUEs). Cross-tier interference is an important issue in this deployment, which may significantly impact signal quality between Macrocell Base Stations (MBSs) and Macrocell User Equipments (MUEs), especially for MUEs near the femtocell. To relieve this problem, the Third Generation Partnership Project Long Term Evolution-Advanced (3GPP LTE-Advanced) de fined the cognitive radio enhanced femtocell to coordinate interference for LTE-Advanced Network. Cognitive radio femtocells have the ability to sense radio environment to obtain radio parameters. In this paper, we investigated the performance of existing schemes based on fractional frequency reuse. Therefore, we proposed a scheme with cognitive radio technology to improve the performance of fractional fre-quency reuse scheme. Simulation results showed that our scheme can effectively enhance average downlink throughput of FUEs as well as the total downlink throughput in LTE-Advanced Networks.